2022
DOI: 10.1149/1945-7111/ac4bf8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Estimations of the Gold Nanoparticle Size Effect on Cysteine-Gold Oxidation

Abstract: Gold nanoparticles are interesting for nanobiomedical applications, such as for drug delivery and as diagnostic imaging contrast agents. However, their stability and reactivity in-vivo are influenced by their surface properties and size. Here, we investigate the electrochemical oxidation of differently sized citrate-coated gold nanoparticles in the presence and absence of L-cysteine, a thiol-containing amino acid with high binding affinity to gold. We found that smaller sized (5, 10 nm) gold nanoparticles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…This small-sized gold nanoparticle has received much attention in recent years in the fields of chemical catalysis, bioimaging, etc. [37][38][39]. In this experiment, we set the concentration of CNGs to 10 mg/mL, at which CNGs are more stable and do not aggregate or settle.…”
Section: Effect Of Chloroauric Acid Concentration On the Morphology O...mentioning
confidence: 99%
“…This small-sized gold nanoparticle has received much attention in recent years in the fields of chemical catalysis, bioimaging, etc. [37][38][39]. In this experiment, we set the concentration of CNGs to 10 mg/mL, at which CNGs are more stable and do not aggregate or settle.…”
Section: Effect Of Chloroauric Acid Concentration On the Morphology O...mentioning
confidence: 99%
“…License: CC BY 4.0 material often used as an immobilisation platform for Cyt c to exploit its ability to induce apoptosis or use as a biosensor due to their biocompatibility and unique optical properties [10,11,[13][14][15][16]. A previous study by Romanovskaia et al found that smaller AuNPs had stronger electrochemical interactions when oxidising with L-cysteine (a thiol-containing amino acids), possibly due to the formation of agglomerates [17], suggesting that the redox ability of a protein like Cyt c could be influenced by the size of the material it is immobilised upon. Ligand exchange is a common way that the functionality of AuNPs can be modulated and is often required for the immobilisation of a protein like Cyt c. Ligand exchange produces three factors that could influence the redox ability of Cyt c, the distance between the surface of the material, the position at which Cyt c is conjugated to the ligand and the method used to conjugate Cyt c to the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this study aimed to identify the physical and electrochemical effects that immobilising Cyt c to AuNPs has upon the redox ability of the protein by varying the conjugation strategies, self-assembled monolayer (SAM) ligands, AuNP size, and presence of other adsorbate molecules. Using circular dichroism (CD) spectroscopy, we observed changes in the secondary and tertiary structures of Cyt c after its conjugation to AuNPs [16,17]. This technique can help monitor any modifications in a protein's structure, such as folding or unfolding [18].…”
Section: Introductionmentioning
confidence: 99%